Evaluation of sentinel events and suicide predictors In X Hospital - Edi Yusuf (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
Sentinel events can result in death in suicide cases perpetrated by patients with mental disorders. The research was conducted using qualitative method. Themes obtained through coding the results of interviews are first: health workers are less alert, second: the ratio of officers and patients unbalanced, third: not yet implemented SPO patient safety by officers, fourth: facilities and infrastructure of mental hospitals that support the case Sentinel suicide, and depression conditions in patients led to a suicide sentinel case. Prevention strategies for suicide sentinel cases include: preliminary early assessment of suicidal risk patients, improvement of infrastructure facilities that support patient safety, improvement of human resources quality with education and training.